15-Deoxy-Δ12, 14-prostaglandin J2 stabilizes hypoxia inducible factor-1α through induction of heme oxygenase-1 and direct modification ofprolyl-4-hydroxylase 2. (2nd October 2016) - Choi, Jee-Eun; Kim, Jung-Hyun; Song, Na-Young; Suh, Jinyoung; Kim, Do-Hee; Kim, Su-Jung; Na, Hye-Kyung; Nadas, Janos; Dong, Zigang; Cha, Young-Nam; Surh, Young-Joon
Abstract: 15-Deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ), a representative J-series cyclopentenone prostaglandin, has biphasic roles in cell proliferation and apoptosis. Hypoxia inducible factor-1 (HIF-1) regulates expression of various genes involved in tumor growth and angiogenesis. In the present study, treatment of human breast cancer (MCF-7) cells with 15d-PGJ2 resulted in the accumulation of the α-subunit of HIF-1. Pretreatment with zinc protoporphyrin IX, a pharmacological inhibitor of heme oxygenase-1 (HO-1), as well as siRNA knockdown of HO-1 gene in MCF-7 cells attenuated 15d-PGJ2 -mediated HIF-1α accumulation. 15d-PGJ2 treatment increased intracellular production of reactive oxygen species (ROS), which was mediated by HO-1 induction. Preincubation of MCF-7 cells with trolox, a water-soluble form of vitamin E, attenuated 15d-PGJ2 -induced HIF-1α expression although HO-1 expression was unchanged. This finding suggests that ROS accumulated as a consequence of HO-1 up-regulation can enhance HIF-1α expression in MCF-7 cells treated with 15d-PGJ2 . Alternatively, 15d-PGJ2 was found to covalently bind to HIF-1α prolyl-4-hydroxylase 2 (PHD2) in MCF-7 cells, which hampers the proline hydroxylation of HIF-1α, thereby disrupting ubiquitin-dependent proteasomal degradation of this transcription factor. Pretreatment with thiol reducing agents blunted 15d-PGJ2 -induced HIF-1α stabilization, indicative of a cysteine residue as a direct target of 15d-PGJ2 . Molecular docking analysis suggests that 15d-PGJ2 preferentially binds to PHD2 in the vicinity of the Cys 201 residue based on binding energies and carbon–sulfur distances. In summary, 15d-PGJ2 stabilizes HIF-1α in MCF-7 cells through HO-1 induction with subsequent ROS generation and also through direct modification of PHD2.